2008
DOI: 10.1128/aem.00455-08
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Patterns in the Microbial Diversity of a Meromictic Soda Lake in Washington State

Abstract: The microbial community diversity and composition of meromictic Soap Lake were studied using culturedependent and culture-independent approaches. The water column and sediments were sampled monthly for a year. Denaturing gradient gel electrophoresis of bacterial and archaeal 16S rRNA genes showed an increase in diversity with depth for both groups. Late-summer samples harbored the highest prokaryotic diversity, and the bacteria exhibited less seasonal variability than the archaea. Most-probable-number assays t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 74 publications
6
52
1
Order By: Relevance
“…2) were consistent with the results of bacterial diversity revealed from the water of four Swedish lakes during cyanobacterial blooms using molecular biological methods (Eiler and Bertilsson, 2004). However, many Böddi-szék clones showed the highest sequence similarities to uncultured environmental clones originating from similar saline and alkaline aquatic environments (Dimitru et al 2008;Humayoun et al 2003;Mesbah et al 2007). In accordance with our results, studying the prokaryotic communities inhabiting the water and sediment of Wadi an Natrun lakes (Egypt), Mesbah et al (2007) also revealed an unexpected phylogenetic diversity and found that none of their rarefaction curves obtained from the analysis of clone libraries reached plateaus.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…2) were consistent with the results of bacterial diversity revealed from the water of four Swedish lakes during cyanobacterial blooms using molecular biological methods (Eiler and Bertilsson, 2004). However, many Böddi-szék clones showed the highest sequence similarities to uncultured environmental clones originating from similar saline and alkaline aquatic environments (Dimitru et al 2008;Humayoun et al 2003;Mesbah et al 2007). In accordance with our results, studying the prokaryotic communities inhabiting the water and sediment of Wadi an Natrun lakes (Egypt), Mesbah et al (2007) also revealed an unexpected phylogenetic diversity and found that none of their rarefaction curves obtained from the analysis of clone libraries reached plateaus.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, the cultivation dependent and independent analyses of planktonic and sediment microbial communities include, among others, studying the soda lakes of South-East Siberia, Russia (Foti et al 2007(Foti et al , 2008, North-East Mongolia (Sorokin et al 2004), Inner Mongolia, China (Zhang et al 2001;Ma et al 2004a), Lonar Lake, India (Wani et al 2006;Joshi et al 2008), the East African Rift Valley, Kenya and Tanzania (Rees et al 2004;Mwirichia et al 2010Mwirichia et al , 2011, Wadi An Natrun, Egypt (Mesbah et al 2007), as well as Mono Lake, California, USA (Hollibaugh et al 2001;Humayoun et al 2003) and Soap Lake, Washington, USA (Dimitru et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Community Composition at a High Taxonomic Level Due to the strong vertical chemical gradients and zonation of redox reactions with depth, a clear vertical stratification of microbial communities is usually observed for meromictic lakes [48][49][50][51]. In spite of the different extraction protocols used, the relative abundances of potentially active and bulk bacterial and archaeal communities were mostly similar at the phylum level, with some notable exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Halanaerobium hydrogeniformans (formerly Halanaerobium sapolanicus) was isolated from haloalkaline (pH ϳ10, 15-to 140-g/liter NaCl), anaerobic sediments of Soap Lake, WA, with extraordinarily high sulfide concentrations of up to 10 g/liter (1,3,8,12). It is an obligately anaerobic, Gram-negative, nonmotile, nonsporulating, elongated rod.…”
mentioning
confidence: 99%